Online Media Reporting Model Encourages Society to Migrate to Digital Broadcasting - Santoso, Puji; Sinaga, Corry Novrica (Communicatus: Jurnal Ilmu komunikasi, 2023)
This research aimed to analyze the implementation of news coverage on the digitalization of broadcasting and explore the online media reporting model for the digitalization of broadcasting in Indonesia. The online media reporting model encourages people to migrate from analogue to digital television platforms. This research employed a descriptive qualitative method to analyze news from the online media www.Detikcom edition November 1, 2022 to November 16, 2022. Additionally, it utilized Nvivo 12+ software for the data analysis. Detikcom was selected as the data source because it had been ranked as one of the top five online news media most accessed by the public, reaching 320.3 million visits. Most smartphone users, approximately 98%, have visited this site. Based on the researchers' analysis, ten media contents of Detikcom reported the transition from analogue to digital television. The research findings suggested that there is a configuration model for online media reporting on broadcast digitalization. In addition, the online media reporting model identifies the dynamics of the shift from analogue to digital television. The dynamic shift is influenced by economic, juridical, technical, and political views. These findings are expected to provide valuable insights for future researchers studying the digital broadcasting ecosystem in Indonesia post-ASO (Analogue Switch-Off) or post-digitalization.